2009
DOI: 10.1159/000236025
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Dependency in Chronic Treatment of Gastroesophageal Reflux Disease: A Randomized Controlled Clinical Trial

Abstract: Background: Despite evidence of the overuse of acid suppressive medication for gastroesophageal reflux disease (GERD), a transfer to noncontinuous therapy after long-term treatment proves difficult. Aim: To quantify the effect of blinded dosage reduction after long-term therapy on symptom control and quality of life while assessing pharmacological and placebo needs. Methods: Primary care patients with a history of GERD and long-term treatment were randomized to daily placebo with pantoprazole rescue (n = 141) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 70 publications
(44 reference statements)
0
21
2
3
Order By: Relevance
“…Therefore, the dose of PPI should be limited to as minimal as required in the long-term management of GERD, especially in the viewpoint of medical economics [105][106][107][108][109]. Furthermore, consideration of the patient's view on treatment efficacy, safety, cost, preference of medication, and frequency should be taken in long-term strategies.…”
Section: Cq: Is An Acid Suppressant Effective For the Treatment Of Gerd?mentioning
confidence: 99%
“…Therefore, the dose of PPI should be limited to as minimal as required in the long-term management of GERD, especially in the viewpoint of medical economics [105][106][107][108][109]. Furthermore, consideration of the patient's view on treatment efficacy, safety, cost, preference of medication, and frequency should be taken in long-term strategies.…”
Section: Cq: Is An Acid Suppressant Effective For the Treatment Of Gerd?mentioning
confidence: 99%
“…The design and methodology of the trial have been described previously [12]. In short, primary care patients with a history of symptoms due to pyrosis, reflux, GORD, hiatus hernia or oesophagitis using chronic PPI for at least a year were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we showed that 52% of GORD patients on long-term, continuous acid suppression were able to switch to less than daily therapy without losing symptom control [12]. As this is the first step towards therapy reduction by applying on-demand or intermittent therapies, it would be helpful to be able to identify eligible patients.…”
Section: Introductionmentioning
confidence: 99%
“…To the naive subjects for the pylori helicobacter, this effect rebound seems to be proportional in the rise of pH during the treatment, while it tends to be masked by the persistent hypochlorhydria observed at the infected patients by the pylori helicobacter [63]. Other multicentral trials, randomized, in double blind showed that less than a third of patients receiving a long-term IPP, succeeded to stop the treatment without an effect on the control of the symptoms and the quality of life, whereas another third passed to a treatment "in the request" [65,66]. Several pathophysiological hypotheses were envisaged to explain this rebound effect on the acid gastric secretion, such as a hypergastrinemia [61] or a hypertrophy and a hyperplasia of the cells of the gastric wall [63].…”
Section: Esophageal Abnormalitiesmentioning
confidence: 99%